Efek Pemberian Ekstrak Daun Moringa oleifera terhadap Kadar Kreatinin dan Gambaran Histopatologi Ginjal Tikus Putih Hiperkolesterolemia - Tristira Rosyida; Dyah Ratna Budiani; Fikar Arsyad Hakim; Riza Novierta Pesik (Universitas Malahayati Lampung, 2022)
ABSTRACT Moringa can be found in some areas of Indonesia and become traditional medicine of South Asia for inflammation, cardiovascular, gastrointestine, hematology, and hepatorenal dissorder. Various compounds with antioxidant potential are found in Moringa leaves, therefore kidney degeneration as a result of hypercholesterolemia and free radicals could be prevented. This study is aimed to understand the effect of Kelor (Moringa oleifera, Lam.) leaves extract to the level of creatinine and histopathological features in the kidneys of hypercholesterolemia rats (Rattus norvegicus). This is a laboratory experimental research using pre and post test with control group design for creatinine measurement and post test only with control group design for histopathology features of kidney, using 28 male rats of Sprague dawley strain. The rats were randomly divided into four groups: control group (KK) were fed with standart pellet, first group (KP1) were hypercholesterolemic rats model without Moringa leaves extract, second group (KP2) were hypercholesterolemic rats model with Moringa leaves extract at dose of 40mg/200gBW, and third group (KP3) were hypercholesterolemic rats model with Moringa leaves extract at dose of 80mg/200gBW. High fat food composition were duck yolk 2cc/200gBW, oxidized oil 1cc/200gBW, and beef tallow 2cc/200gBW. Creatinine level was analyzed with paired T-test and Wilcoxon tests. The histopathological features of the kidney were evaluated based on hydropic degeneration and lipid degeneration of the tubules, analyzed with Mann-Whitney test. There was a significant difference based on Paired T Test between the mean of creatinine level before-after intervention of high fat food (p0.05), and before-after intervention of Moringa leave extract based on Wilcoxon Test (p0.05). Kruskal Wallis Test showed that there were difference between 4 groups (p0.05). Mann Whitney posthoc test of hydropic degeneration showed differences between KK-KP1, KP1-KP2, KP1-KP3 (p0.05). However, the result of Moringa oleifera leaves extract intervention in lipid degeneration of the tubules was insignificant based on Mann Whitney posthoc test (p0.05). Moringa oleifera leaves extract dose of 40mg/200gBW and 80mg/200gBW significantly decreased the creatinine level and improved histopathological features of the kidney in hypercholesterolemic Sprague dawley rats (Rattus norvegicus). Keywords: Moringa leaves Extract, Creatinine Level, Histopathology of Kidney, Hypercholesterolemia ABSTRAK Tanaman Kelor (Moringa oleifera, Lam.) dapat dijumpai di berbagai daerah di Indonesia dan dijadikan sebagai pengobatan tradisional Asia Selatan untuk peradangan, kardiovaskuler, gastrointestinal, hematologi dan gangguan hepatorenal. Berbagai senyawa berpotensi antioksidan terkandung dalam daun kelor sehingga degenerasi ginjal akibat hiperkolesterolemia dan radikal bebas dapat dicegah. Tujuan penelitian ini adalah untuk meneliti efek pemberian ekstrak etanolik daun kelor (Moringa oleifera, Lam.) terhadap kadar kreatinin dan gambaran histopatologi ginjal tikus putih (Rattus norvegicus) hiperkolesterolemia. Penelitian dengan metode eksperimental laboratorik dengan rancangan pre and post test with control group design untuk parameter kadar kreatinin dan post test only with control group design untuk parameter histopatologi ginjal pada 28 sampel tikus putih jantan strain Sprague dawley. Sampel dibagi dalam empat kelompok, Kelompok Kontrol (KK) diberi pakan standar, kelompok I (KP1) diberi pakan tinggi lemak, Kelompok II (KP2) diberi pakan tinggi lemak dan ekstrak etanolik daun kelor dosis 40mg/200gBB, serta kelompok III (KP3) diberi pakan tinggi lemak dan ekstrak etanolik daun kelor dosis 80mg/200gBB. Komposisi pakan tinggi lemak yakni 2cc/200gBB kuning telur bebek, 1cc/200gBB minyak teroksidasi, dan 2cc/200gBB lemak sapi. Kadar kreatinin dianalisis dengan One-Way ANOVA, uji T berpasangan, dan Wilcoxon. Histopatologi ginjal dinilai berdasarkan degenerasi hidropik dan degenerasi lemak tubulus dengan analisis Mann Whitney. Diperoleh hasil bermakna dari hasil uji T berpasangan pada kadar kreatinin darah antara sebelum dan setelah pemberian pakan tinggi lemak (p0,05), dan hasil uji Wilcoxon pada kadar kreatinin darah antara sebelum dan setelah pemberian ekstrak etanolik daun kelor (p0,05). Hasil uji Kruskal Wallis diperoleh perbedaan bermakna pada keempat kelompok (p0.05). Hasil uji Mann Whitney pada degenerasi hidropik tubulus ginjal didapatkan adanya perbedaan bermakna antara KK-KP1, KP1-KP2, KP1-KP3 (p0,05). Namun, pemberian ekstrak etanolik daun kelor terhadap degenerasi lemak tubulus ginjal tidak bermakna menurut hasil uji Mann Whitney (p0,05). Ekstrak etanolik daun kelor dosis 40 mg/200gBB dan dosis 80 mg/200gBB menurunkan kadar kreatinin dan memperbaiki gambaran histopatologi ginjal tikus putih (Rattus norvegicus) hiperkolesterolemia secara bermakna. Kata Kunci: Ekstrak Daun Kelor, Kreatinin, Histopatologi Ginjal, Hiperkolesterolemia